Study on effect of heavy metals toxin to water and some creatures in surrouding areas of general laboratories - Hong Van, Luong Thi (Academia Journal of Biology, 2012)
In this research, the authors carried out analyses the total content of As, Hg, Cd, Pb, Fe and Mn in water (well-water and pond-water) and in biological samples (Vegetables and animals) by AAS and Metrohm 797 VA computrace. The results showed that the content of As, Hg, Cd, Pb, Fe, Mn in water samples of the study area is higher than their content in control area from 1.25 to 7.7 times (p < 0.05). Especially, the content of As, Hg, Cd and Pb was higher than allowable standard from 5.0 to 23.4 times. Vegetables were polluted by heavy metals. The content of As, Hg, Cd, Pb, Fe, Mn was higher than their content in control area from 1.24 to 265.0 times (p < 0.05). Some of them such as: As, Pb and Cd were higher than allowable standard from 1.3 to 3.5 times. Animals were polluted by heavy metals, too. The content of As, Hg, Cd, Pb, Fe and Mn was higher than their content in control area from 1.1 to 58.0 times (p < 0.05). But all of them were lower than allowable standard. There was a very close correlation between the content of heavy metals in animals, vegetables and their content in water